Scheme Reflections aimed at Positioning Submerged Radar Networks - Senthamizh Rajan, N; Mala, R (International Journal of Computer Sciences and Engineering, 2025)
The reliance of submerged network deployments on specialized hardware for acoustic communication and modulation has impeded wide scale deployments of submerged sensor networks. This paper examines a system that integrates software modems with generic speakers and microphones that are built-in to sensor modules for establishing submerged acoustic links. Building on our recent field experiment in a river, canal, pond, and swimming pool, this paper outlines the technical and logistical challenges for deploying software-driven submerged sensor network. The software modem design choices include methods for signal modulation at the sender, and symbol synchronization, signal filtering, and signal demodulation at the receiver. Higher layer communication protocol issues are also discussed, with a focus on cross-layer optimization. Practical solutions to logistical deployment challenges, such as waterproofing and casing, calibration, and fouling are proposed. The design guidelines in this paper lay the groundwork for further development of software-driven of submerged sensor networks.